Relationship of Education, Knowledge, and Perception with Stigma Tward PLWHA in Malawili Village, Sorong - Lidia Eklesia Mora; Yanti Pesurnay; Sariana Pangaribuan (International Journal Of Health Science, 2025)
Human Immunodeficiency Virus (HIV) is a virus that attacks the immune system, specifically on white blood cells, namely CD4 cells. The most advanced stage of HIV infection is Acquired Immunodeficiency Syndrome (AIDS). The level of education can influence people's way of thinking about stigma.Knowledge and perceptions can influence attitudes and behavior towards PLWHA. People living with HIV will face various stigmatizations can affect the emotional well-being and mental health of PLWHA. The research design used is observational analytic study with a cross-sectional design. The study was conducted in RW 03, Malawili Village, Sorong Regency, the research sample was 195 people selected by proportional random sampling method. The research instrument is a questionnaire. The data obtained was then analyzed by chi-square. Research results obtained the majority of respondents had a secondary education level, namely 91 people (46,7%), the majority of respondents had a good level of knowledge, namely 135 people (62,2%), the majority of respondents had a negative perceptions, namely 99 people (50,8%), and the majority of respondents were in the not stigmatizing category, namely 114 people (58,5%). Based on these results, it can be concluded that there is a significant relationship between the level of education, knowledge and perceptions with Community Stigma Towards People Living With HIV/AIDS (PLWHA) in RW 03 Malawili Village, Sorong Regency.